2020
DOI: 10.1007/s11270-020-04885-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Woodchip Biochar and Brown Coal Waste as Stable Sorbents for Abatement of Bioavailable Cadmium, Lead and Zinc in Soil

Abstract: Organic sorbents alter physicochemical soil properties and mitigate heavy metal (HM) bioavailability. However, some sorbents are labile and, therefore, introduce the risk of HM release into soil after mineralisation. Before field application, new stable organic sorbents such as woodchip biochar (BIO) and brown coal waste (BCW) need to be tested and compared with standard organic amendments like farmyard manure (FYM). An incubated pot experiment was conducted to investigate the efficacy of FYM, BIO and BCW (add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Omotade et al [43] applied biochar of maize cobs, peanut shells, cow dung, and poultry litter pyrolyzed at 300-600 • C for 3 h. Results from this research showed that the highest contents of N (0.62%) and K (16.2 mg g −1 ) were found in cow dung, P (66.4 mg g −1 ), Mg (0.28%), and sulfur (S; 0.28%) in maize cob, and Ca (4.21 mg g −1 ) in peanut shell. Thus, wood-based biochars are suitable when the final objective is carbon storage in soil [44,45], while biochars from animal manures and grasses are used when the objective is to increase the soil N, P, K, Ca, Mg, and S contents [45,46]. According to Ippolito et al [47], biochars produced from hardwoods supply 0.002, 2.2 and 17% of the total N, total P, and total K, respectively, while biochars of soft softwoods can supply 27% total P and 6% K [47].…”
Section: Biochar Feedstock Sourcesmentioning
confidence: 99%
“…Omotade et al [43] applied biochar of maize cobs, peanut shells, cow dung, and poultry litter pyrolyzed at 300-600 • C for 3 h. Results from this research showed that the highest contents of N (0.62%) and K (16.2 mg g −1 ) were found in cow dung, P (66.4 mg g −1 ), Mg (0.28%), and sulfur (S; 0.28%) in maize cob, and Ca (4.21 mg g −1 ) in peanut shell. Thus, wood-based biochars are suitable when the final objective is carbon storage in soil [44,45], while biochars from animal manures and grasses are used when the objective is to increase the soil N, P, K, Ca, Mg, and S contents [45,46]. According to Ippolito et al [47], biochars produced from hardwoods supply 0.002, 2.2 and 17% of the total N, total P, and total K, respectively, while biochars of soft softwoods can supply 27% total P and 6% K [47].…”
Section: Biochar Feedstock Sourcesmentioning
confidence: 99%
“…The benefits of HAs in soil are far-ranging and are well reported in the literature, including improvement of soil structure (water holding capacity, aeration, and aggregation) and promotion of plant growth through biostimulation (enzymatic activation, microbial growth stimulation, and root elongation) [12,14,15]. This highlights the suitability of HA-rich organic amendments for both environmental and agricultural applications [1,10,16].…”
Section: Introductionmentioning
confidence: 73%
“…The amendment of agricultural and marginal soils with organic materials increases soil organic matter (SOM), enhancing soil resilience through improvements in soil physical, chemical, and biological properties [1][2][3]. Organic residues in soil are biologically transformed to their inorganic forms via mineralisation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, humic and fulvic acids acquire a negative charge and combine with positively charged ions (cations) to form organomineral compounds [47][48][49]. The formation of chelated complexes with cations of heavy metals contributes to soil detoxication and increases the availability of plant nutrients [50][51][52][53][54]. The effect of Rekulter on reducing the uptake of Zn, Pb, and Cd by plants presented in Table 3.…”
Section: R-cooh + Ohmentioning
confidence: 99%